The cell - Thompson, Andrew (London : BBC, 2009)
Embark on compelling, mind-blowing, and complex journey through 300 years of history to discover the secrects of the cell - and of life itself. In this fascinating series, Dr. Adam Rutherford delves back through time to the first observations of the cellular structure of plants ; the search for the secrect of life that led scientists deep into the inner workings of the cell ; and to modern research in synthetic biology that could see us to create life from scratch
ep.1. The hidden kingdom.- ep.2. The chemistry of life.- ep.3. The spark of life.
Executive producer, Marcus Herbert ; editor, Jonathan Seal
Presenter, Dr. Adam Rutherford
dvd format
Keywords: Cells; Cytology -- History; Biochemistry -- History; Life -- Origin